Cultural competence and its related factors in health care providers working in comprehensive health centers affiliated with Tehran university of medical sciences - Leila Nafar; Reza Negarandeh; Naeimeh Sarkhani; Nasrin Nikpeyma (Tehran University of Medical Sciences, 2022)
Background & Aim: Cultural competence is one of the main components of health care. Attention to cultural competence is essential to reduce healthcare inequalities and identify potential for improving healthcare delivery. The aim of this study was to investigate cultural competence and its related factors in health care providers working in comprehensive health centers affiliated with Tehran University of Medical Sciences (TUMS). Methods & Materials: In this descriptive, cross-sectional study, 250 health care providers working in health centers affiliated with TUMS were selected using the convenience sampling method in 2020. The demographic characteristics form and the cultural competence scale for health workers (CCSN) were used to collect the data. Data were analyzed using descriptive and inferential statistical tests (t-test and ANOVA) through the SPSS software version 16 at a significance level of 0.05. Results: The mean total score of cultural competence in health care providers was 162.66±28.41 (range: 33-231). According to the findings, the mean score of cultural competence for all dimensions was desirable. The mean score of cultural competence had a statistically significant relationship with intra-ethnic marriage (P>0.005) and work experience (P=0.012) while no statistically significant difference was observed with other demographic variables. Conclusion: The study results showed that cultural competence in health care providers was at the desirable level. These results may be useful for managers and planners in the development and management of human resources and quality assurance of health services delivery.